Sulfated Laminarin Polysaccharides Reduce the Adhesion of Nano-COM Crystals to Renal Epithelial Cells by Inhibiting Oxidative and Endoplasmic Reticulum Stress - Tian-Qu He; Zhi Wang; Chuang-Ye Li; Yao-Wang Zhao; Xin-Yi Tong; Jing-Hong Liu; Jian-Ming Ouyang (MDPI AG, 2024)
Purpose: Adhesion between calcium oxalate crystals and renal tubular epithelial cells is a vital cause of renal stone formation; however, the drugs that inhibit crystal adhesion and the mechanism of inhibition have yet to be explored. Methods: The cell injury model was constructed using nano-COM crystals, and changes in oxidative stress levels, endoplasmic reticulum (ER) stress levels, downstream p38 MAPK protein expression, apoptosis, adhesion protein osteopontin expression, and cell-crystal adhesion were examined in the presence of Laminarin polysaccharide (DLP) and sulfated DLP (SDLP) under protected and unprotected conditions. Results: Both DLP and SDLP inhibited nano-COM damage to human kidney proximal tubular epithelial cell (HK-2), increased cell viability, decreased ROS levels, reduced the opening of mitochondrial membrane permeability transition pore, markedly reduced ER Ca2+ ion concentration and adhesion molecule OPN expression, down-regulated the expression of ER stress signature proteins including CHOP, Caspase 12, and p38 MAPK, and decreased the apoptosis rate of cells. SDLP has a better protective effect on cells than DLP. Conclusions: SDLP protects HK-2 cells from nano-COM crystal-induced apoptosis by reducing oxidative and ER stress levels and their downstream factors, thereby reducing crystal-cell adhesion interactions and the risks of kidney stone formation.